Advanced microporous membranes for H2/CH4 separation: Challenges and perspectives - Zhou, Rongfei; Pan, Yichang; Xing, Weihong; Xu, Nanping (Advanced membranes, 2021)
The utilization of hydrogen is regarded as the effective approach to arrive at the global carbon-neutrality target. Hydrogen/methane separation is a necessary unit for the hydrogen production in the petroleum industry. The development of high-performance membranes with high thermal, chemical and mechanical stabilities are an important issue for hydrogen membrane separation. This review provides an overview of current research on the process of membrane preparation and their separation performance toward H2/CH4 mixtures for the advanced microporous membranes that own high separation performance and high durability. Typical advanced microporous membranes including zeolite, metal organic framework, carbon-based and polymer-based microporous membranes were summarized for H2/CH4 separations. The current challenges and future perspectives towards the industrial application of advanced microporous membranes for H2/CH4 separation are outlined. [Display omitted] •Research processes of zeolite, MOF, carbon-based and polymeric-based microporous membranes are reviewed.•Membrane preparation method and H2/CH4 separation performance of these advanced microporous membranes (AMMs) are included.•Challenges on the development of AMMs for actual H2/CH4 separations are summarized.•The future perspectives on the improvement of separation performance and stability of AMMs are outlined.